Comparison of the Principle of Freedom of Contract in Land Buying and Selling Between Indonesia and Malaysia - Salsabila, Erdhyna‘Afifah; Suwadi, Pujiyono; Suryono, Arief (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The transfer of land rights can occur through buying and selling, inheritance, gifting, or exchanging. The process of transferring rights, especially through buying and selling, according to the National Land Law in Indonesia, differs from other countries, such as Malaysia, because Indonesia fundamentally has a different concept of land law compared to Malaysia. The aim of this research is to analyze the comparison of the principle of freedom of contract in land buying and selling between Indonesia and Malaysia. This study employs normative legal research that examines the legal system. Systematic legal research is conducted on written laws or regulations related to the chosen topic. The author uses primary and secondary legal materials. The research results indicate that land buying and selling in Indonesia and Malaysia are in line with and not contrary to the principle of freedom of contract. This is because if an agreement meets the valid requirements, meaning it is made with the agreement of the involved parties, the subject of the agreement is capable of entering into an agreement, the object is clear, and the cause is not prohibited.